Practical Person‐Specific Eye Rigging. (7th June 2019) - Bérard, P.; Bradley, D.; Gross, M.; Beeler, T.
Abstract: We present a novel parametric eye rig for eye animation, including a new multi‐view imaging system that can reconstruct eye poses at submillimeter accuracy to which we fit our new rig. This allows us to accurately estimate person‐specific eyeball shape, rotation center, interocular distance, visual axis, and other rig parameters resulting in an animation‐ready eye rig. We demonstrate the importance of several aspects of eye modeling that are often overlooked, for example that the visual axis is not identical to the optical axis, that it is important to model rotation about the optical axis, and that the rotation center of the eye should be measured accurately for each person. Since accurate rig fitting requires hand annotation of multi‐view imagery for several eye gazes, we additionally propose a more user‐friendly "lightweight" fitting approach, which leverages an average rig created from several pre‐captured accurate rigs. Our lightweight rig fitting method allows for the estimation of eyeball shape and eyeball position given only a single pose with a known look‐at point (e.g. looking into a camera) and few manual annotations.